2021
DOI: 10.1038/s41380-021-01379-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide interaction study with major depression identifies novel variants associated with cognitive function

Abstract: Major Depressive Disorder (MDD) often is associated with significant cognitive dysfunction. We conducted a meta-analysis of genome-wide interaction of MDD and cognitive function using data from 4 large European cohorts in a total of 3510 MDD cases and 6057 controls. In addition, we conducted analyses using polygenic risk scores (PRS) based on data from the Psychiatric Genomics Consortium (PGC) on the traits of MDD, Bipolar disorder (BD), Schizophrenia (SCZ), and mood instability (MIN). Functional exploration c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 71 publications
(84 reference statements)
1
11
0
Order By: Relevance
“…The fifth replicated protein, tumor necrosis factor receptor superfamily member 21 (TNFRSF21), plays a role in neuronal apoptosis and the negative regulation of oligodendrocyte maturation [42]. The TNFRSF21 gene has been found to be differentially expressed in PTSD [43,44], including in postmortem brain samples in orbitofrontal cortex and dorsal anterior cingulate cortex regions [17], and genetic variants within this gene have emerged in genome-wide association studies of panic disorder [45] and depression [46,47]. Finally, DRAXIN a role in neural development and has been implicated in autism spectrum disorder and obsessive-compulsive disorder [48].…”
Section: Discussionmentioning
confidence: 99%
“…The fifth replicated protein, tumor necrosis factor receptor superfamily member 21 (TNFRSF21), plays a role in neuronal apoptosis and the negative regulation of oligodendrocyte maturation [42]. The TNFRSF21 gene has been found to be differentially expressed in PTSD [43,44], including in postmortem brain samples in orbitofrontal cortex and dorsal anterior cingulate cortex regions [17], and genetic variants within this gene have emerged in genome-wide association studies of panic disorder [45] and depression [46,47]. Finally, DRAXIN a role in neural development and has been implicated in autism spectrum disorder and obsessive-compulsive disorder [48].…”
Section: Discussionmentioning
confidence: 99%
“…A step in this direction has been made by Thalamuthu and colleagues [ 54 ] who investigated the interaction between MDD and genetic variants on different domains of cognition in a GWAS approach. Although their measurements of current MDD and cognition were very heterogeneous and they could not measure APOE ε4 status directly, they were able to identify the amyloid precursor protein network as an important mechanism for executive function in a considerably large sample.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SCZ, a GWAS of MDD and cognitive function found that there were 48, 116, and 32 SNPs significantly associated with executive function domains, processing speed, and global cognition, respectively. Some of these SNPs are located in genes expressed in brain with important roles in neuronal development (REST), oligodendrocyte maturation (TNFRSF21) and myelination (ARFGEF1) ( Thalamuthu et al, 2022 ). A large GWAS combining data on SCZ ( n = 82,315), BD ( n = 51,710), and general intelligence ( n = 269,867) identified 75 distinct genomic loci associated with SCZ and intelligence, and 12 loci associated with BD and intelligence.…”
Section: Geneticsmentioning
confidence: 99%